Penggunaan Sarana Prasarana untuk Meningkatkan Prestasi pada Atlet Bola Basket di Club Ranggajati Cirebon (Universitas Negeri Semarang, 2022)
The purpose of this study was to determine the use, maintenance, and supervision of the infrastructure. This study uses interviews and observations and then triangulates the data to determine the use, maintenance, and supervision of infrastructure. The result of this study is the utilization of the facilities and infrastructure of the Ranggajati Basketball Club to provide facilities according to standards, except for non-standard fields and shoes that are still owned by athletes. For infrastructure maintenance, the Ranggajati club is good. Facility maintenance is carried out by cleaning and periodic inspections of the basketball court and hoop infrastructure. Supervision of the facilities and infrastructure of the Ranggajati basketball club is carried out to evaluate the findings of the facilities and infrastructure so that they become reference materials in treatment. The local government must review the procurement of basketball courts in Gor Ranggajati according to national standards. Local governments are also expected to pay special attention to other sports so that they can develop and reap achievements.